Analysis of the Cost Structure of the Construction Safety Management System for School Infrastructure Projects Based on Work Breakdown Structure - Siringoringo, Yosia Suwadi; Machfudiyanto, Rossy Armyn (Avenew Indonesia, 2025)
The Rehabilitation and Renovation of School Infrastructure program was initiated by the Indonesian Government through the Ministry of Public Works and Housing in 2019. Within this program, school categorized as low-risk buildings. However, field data show that construction-related accidents still occur frequently during implementation. This phenomenon is presumed to result from inadequate construction safety planning, particularly in the budgeting of Construction Safety Management System (CSMS) components. The main purpose of this research is to create a Work Breakdown Structure (WBS), pinpoint hazards and risks, propose strategies to mitigate these risks, outline objectives and plans, and establish cost factors in order to compute the percentage of CSMS expenditures associated with school restoration and refurbishment projects. A quantitative research method was employed to construct the questionnaire instruments from the initial to the final stage, starting with a literature review. Five construction safety experts validated these instruments. Risk levels were qualitatively assessed (Frequency × Severity) based on the evaluations of 30 respondents. The novelty of this research lies in its specific focus on school infrastructure as the project object. The Ministry of Public Works' school reconstruction and refurbishment initiatives necessitate budget allocations spanning from 2.63% to 4.52% of the Engineer's Estimate for CSMS expenditures.